P17.08.B Single institutional retrospective review of re-irradiation in High Grade Gliomas in a tertiary UK centre. (5th September 2022) - Manik, V; Brazil, L; Swampillai, A; Chia, K; Al-Salihi, O
Abstract: Background: Recurrent high grade gliomas (HGG) pose a treatment challenge as no definite guidelines exist. Re-excision could be appropriate in some cases while systemic therapy options are only a handful. We thus need to resort to the option of re-irradiation at some point but there could be a wide variety of techniques, volumes & doses to choose from due to lack of robust evidence. The UK wide BRIOCHe study for Glioblastoma Multiforme (GBM) will help in providing some standardisation. With this retrospective study, we aim to review our institutional practice with re-irradiation & our patient outcomes. Material and Methods: Electronic health records over a period of 3 years from 1 Jun 2019 to 30 May 2021 were searched for patients with HGG that underwent a course of re-irradiation. Various patient factors, tumour & treatment factors at baseline and at recurrence and survival data were collected. Results: Total of 8 patients received re-irradiation with all except one having a performance status of 1 at the time of treatment. Seven patients had GBM, one had transformation from baseline G2 glioma and the eighth patient had anaplastic oligodendroglioma (ODG). MGMT was methylated in 62.5% patients while IDH mutation was present only in the transformed glioma. Majority patients had radiotherapy dose of 60Gy/30 fractions with concurrent temozolomide (TMZ) at baseline to a median CTV volume of 186cc. A median of 6 cycles of TMZ were given in the adjuvant setting. Median time to recurrence from completion of adjuvant treatment was 6.7 months (range: 0.9 - 171.6 months). Most recurrences were in the same or an adjacent lobe whereas 1 patient had a multi-focal recurrence. Half the patients at recurrence underwent a re-resection. All patients had salvage chemotherapy at the time of recurrence with a median of 2 regimens and a median of 6 cycles prior to re-irradiation. All patients received a re-irradiation dose of 35Gy in 10 fractions to a median CTV volume of 149cc. The median interval from previous radiotherapy was 18.9 months (range: 11.6 - 190.5 months). The median time to progression from re-RT was 5.4 months (CI: 3.4 - 7.4) and median survival from re-RT was 7 months (CI: 6.2 - 7.8). The median overall survival since diagnosis was 35.1 months (CI: 22.2 - 48.1), one patient was lost to follow up. Conclusion: Re-irradiation is a safe & feasible treatment option in carefully selected cases of high grade glioma.